Study on Development of an Automatic Wind Turbine System - Hoq, Enamul; Mashud, Mohammad; Rahman, Md Mizanur; Islam, Md. Shariful (SciEn Conference Series: Engineering, 2025)
The most swiftly expanding renewable energy source for electricity production is wind power, which is one of the three primary renewable energy sources, along with solar and hydropower. Wind energy is abundant and can supply electricity to a significant portion of the world; however, it is unpredictable and sporadic, which makes it difficult to rely solely on it. Ultimately, the objective of this project is to create and implement an autonomous wind turbine system that can detect wind direction and adjust its orientation accordingly. As a result, we integrate wind from a diverse array of directions, including 0 degrees to 120 degrees, into the traditional sensor-based wind turbine design. By monitoring wind orientation and operating the wind turbine, the wind direction sensor preserves the same efficiency as the direct model's. Our research also indicates that sensor-based wind turbines operate at nearly twice the average efficiency of conventional wind turbines. Regardless of the wind conditions, the objective of this endeavor is to establish the article as a cost-effective alternative power source.  Due to improved technologies and reliability, the advantages of the swiftly expanding renewable energy source have a minimal environmental impact.